Analysis of the evolution of the adhesion of firms to the corporate sustainability index (ISE) - Crisóstomo, Vicente Lima; Gomes, Lorena Albuquerque da Silva; Braga, Célia (Revista de Administração da UFSM, 2018)
Under the frameworks of the Voluntary Disclosure and Stakeholder Theoriesy this work aims to analyze the evolution, the adherence and the continuity of firms in the Corporate Sustainability Index (ISE) of B3. Methodology is based on content analyses of the ISE questionnaire, descriptive analysis, and tests for the difference in proportions. The analysis was based on all 72 firms that have already composed the ISE portfolio. Results show a growing interest of firms to integrate the ISE index given the annual increase in the number of companies. The findings indicate a significant proportion of firms that remain in ISE portfolio in consecutive years. Similarly, the proportion of firms that allow making public the content of their questionnaire is also significant. In addition, it is important to highlight the dimensions of the ISE questionnaire which inquires about firm policies beyond the typical social dimension of Corporate Social Responsibility, i.e. the social dimension. In fact, the ISE index comprises strongly the Corporate Governance and Economic dimensions of CSR.